Developing EZH2 Targeted Therapy for Lung Cancer - Frankel, Arthur E. (Cancer Discov, 2016)
Epigenetic targets are exciting new avenues for cancer drug discovery. Zhang and colleagues have designed the open-source EZH2 inhibitor JQEZ5 and shown anti-tumor efficacy in vitro and in vivo in preclinical studies in murine and human lung adenocarcinomas models expressing high levels of EZH2 (1).